Interpreting volatility shocks as preference shocks - Shaofeng Xu (Bank of Canada, 2016)
This paper examines the relationship between volatility shocks and preference shocks in an analytically tractable endogenous growth model with recursive preferences and stochastic volatility. I show that there exists an explicit mapping between volatility shocks and preference shocks, and a rise in volatility generates the same impulse responses of macroeconomic aggregates as a negative preference shock.
Keywords: E2; E3; 330; Business fluctuations and cycles; Economic models